Biological Efficacy of Mycoflora Isolated from Mushroom Substrate Against Pathogenic Fungi - Sarker, MAR; Sultana, N; Akhter, K (SAARC Journal of Agriculture, 2022)
Four fungi isolates, Aspergillus flavus, Aspergillus niger, Trichoderma harzianum, Penicillium sp. were isolated from mushroom substrates and identified. Biological activities these fungi were evaluated against three plant pathogens namely against Fusarium oxysporum, Sclerotium rolfsii, Colletotrichum corchori. Among the fungal isolates, Trichoderma harzianum showed the highest antagonistic activity against all three pathogens, Penicillium sp. showed less significant antagonistic activity than Aspergillus niger and Aspergillus flavus. Trichoderma harzianum showed the highest inhibitory effect in case of Fusarium oxysporum (71.75%) followed by Sclerotium rolfsii (61.64%) and Colletotrichum corchori (57%). SAARC J. Agric., 19(2): 73-84 (2021)